Understanding as explaining: how motives can become causes - Fuchs, Thomas (Phenomenology and the cognitive sciences, 2023)
The distinction of „understanding“ and „explaining“, formulated by Karl Jaspers in his „General Psychopathology“, has had a lasting effect on psychiatry. As a result, phenomenological, hermeneutic, or psychodynamic approaches have often been accorded only descriptive or epiphenomenal status, while the actual causes of mental illness have been sought in neurobiologically or genetically based explanations. In contrast, this paper defends the explanatory role of understanding and phenomenological approaches. To this end, two levels of explanation are distinguished and shown to be equally justified in principle, namely, motivational explanation at the macro-level and physical explanation at the micro-level. The actual causal role of motivational, i.e., understandable connections is then demonstrated by means of a conception of circular causality, which includes downward causality. Finally, the explanatory role of phenomenological analyses is also shown in psychotic disorders that refuse motivational understanding, using the example of schizophrenic delusion.
Online veröffentlicht: 30. Juni 2022
Gesehen am 28.08.2024